Evaluación de impacto ambiental de la actividad de extracción de material pétreo en la parroquia Yanayacu cantón Salcedo, provincia Cotopaxi periodo 2015 - Dávalos Constante, Santiago Agustín (2016)
Various methods such as cause-effect matrix for the identification of potential impacts, Leopold Matrix for assessment of the impacts identified in the first phase were applied in this research supported by the use of various techniques, such as: direct observation and field visit that were necessary to perform accurate measurements with technically and qualified equipment to confirm the data obtained by the matrixes. The devices were GPS and sound level meter which could compare sound exposure levels and permissible limits in the labor and environmental fields; pump particles allowed to evaluate air quality by comparing the presence of suspended particles with the limits established in the legislation.